The Impact of Enterprise Resource Planning (ERP) Software Implementation and System Quality on Service Quality at Oriskin Clinics (A Case Study of Three Oriskin Clinic Branches) - Nafisah Oktavianti; Ni Made Widhi Sugianingsih; Wahyudi Utomo; Nuria Puspitasari; Nidia Sofa (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The digital transformation of healthcare service organizations requires integrated information systems capable of improving operational efficiency, data accuracy, and service quality. This study examined the effects of Enterprise Resource Planning (ERP) software implementation and system quality on service quality at three Oriskin Clinic branches located in Sentul, Karawang, and West Jakarta. An empirical quantitative design with an explanatory approach was employed. The study involved all 86 employees using the ERP system through a saturated sampling technique. Primary data were collected using a structured Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption testing, multiple linear regression, coefficient of determination, t-test, and F-test with IBM SPSS Statistics version 27. The results indicate that ERP software implementation has a positive and significant effect on service quality (β = 0.535, p = 0.001), while system quality also exerts a positive and significant effect (β = 0.409, p = 0.001). Simultaneously, both variables significantly influence service quality (F = 1841.430, p = 0.001) and explain 97.8% of its variance (R² = 0.978). These findings demonstrate that effective ERP implementation supported by high system quality substantially enhances operational performance and healthcare service quality in digitally integrated clinical environments.